Prognostic factors of hemorrhagic complications after oxaliplatin-based hyperthermic intraperitoneal chemotherapy: Toward routine preoperative dosage of Von Willebrand factor?. Issue 6 (June 2017) - Delhorme, J.-B.; Sattler, L.; Severac, F.; Triki, E.; Gross, I.; Romain, B.; Rohr, S.; Grunebaum, L.; Brigand, C.
Abstract: Background: Oxaliplatin-based hyperthermic intraperitoneal chemotherapy (HIPEC-ox) induces specific morbidity with hemorrhagic complications (HC). The aim of this study was to identify preoperative, intraoperative and postoperative HC predictive factors after HIPEC-ox. Methods: A prospective single center study that included all consecutive patients treated with curative-intent HIPEC-ox, whatever the origin of peritoneal disease, was conducted. All patients underwent systematic blood tests exploring primary hemostasis and endothelial activation before surgical incision (D0) and on postoperative days 2 (POD2) and 5 (POD5). Results: Between May 2012 and August 2015, 47 patients were enrolled in the study. The overall HC rate was 38%. Major morbidity was significantly higher in patients with HC. Patients presenting HC were significantly more often affected with pseudomyxoma peritonei and had less preoperative chemotherapy. Multivariate analysis showed that a higher plasmatic level of Von Willebrand factor antigen at D0 (D0 VWF:Ag) was a protective predictive factor for HC (p = 0.049, HR: 0.97 CI 95% [0.94–1.00]). A D0 VWF:Ag level below 138% had a sensitivity of 87.5%, a specificity of 67% and an area under the curve of 80.3% (CI 95% [66.5–94], p < 0.01) for predicting HC. Conclusions: Through the identification of prognostic factors, this study highlighted a subgroup of patients with low risk of HC after HIPEC-ox. Based on these results, we propose a routine preoperative dosage of VWF that would help the surgeon to select the most suitable patients for HIPEC-ox.